The effect of explorative and exploitative skills on innovation process during the merger of public research organizations - Kirana Rukmayuninda Ririh; Machfud; Elisa Anggraeni; Nurul Rochman; Nosica Rizkalla (Problems and Perspectives in Management)
This study aims to analyze the effects of explorative and exploitative skills, along with the moderating role of knowledge vacuum, on innovation process and performance during the merger of public research organizations (PROs) to better comprehend these organizational factors. During the merger of PROs, explorative and exploitative skills can prevent a slow innovation process and knowledge loss. Meanwhile, innovation also serves as PRO’s core activity. However, the effect of explorative and exploitative skills (and also the knowledge vacuum) on the innovation process in PROs is still debatable, as they often disregard the knowledge loss effect. This study used 314 questionnaires, which were responded to by scientists of basic and technological research in Indonesia’s merged PRO, namely the National Research and Innovation Agency (BRIN). Data were collected from 2023 to 2024 and analyzed using structural equation modeling (SEM) with Smart-PLS 4.0. The results reveal that the knowledge vacuum has a positive and significant influence on both exploratory-exploitative skills and absorptive-adaptive capabilities of scientists, which will eventually shape their distinctive competencies differently. However, despite the positive influence of the knowledge vacuum, the organization needs to strengthen scientists’ explorative and exploitative skills by reinforcing strategic human resource management through periodic training, performing joint activities or active innovation hubs, and guiding scientists to cope with the dynamic transition periods due to mergers. All of them aim to reinforce knowledge exchange and research networks. AcknowledgmentThis study had no funding and did not employ artificial intelligence. This article is original and was not published in any other language or concurrently submitted to other journals. This study is also clear from reuse of any material. Acknowledgments are expressed to all scientists in National Research and Innovation Agency that voluntarily participated in this study.